Unusual Cause of Esophageal Obstruction in a Neonate Presenting as Esophageal Atresia - Vijay C Pujar; Shirin S Joshi; Sangappa M Dhaded (EL-Med-Pub, 2013)
Esophageal atresia is the commonest cause of obstruction to esophageal lumen in neonates. Foreign bodies in newborns are extremely rare. We report a rare case of esophageal obstruction closely mimicking atresia due to foreign bodies inserted in a female neonate with homicidal intension.